Long-term stability of Au nanoparticle-anchored porous boron-doped diamond hybrid electrode for enhanced dopamine detection. (1st May 2018) - Mei, Xueru; Wei, Qiuping; Long, Hangyu; Yu, Zhiming; Deng, Zejun; Meng, Lingcong; Wang, Jian; Luo, Jingting; Lin, Cheng-Te; Ma, Li; Zheng, Kuangzhi; Hu, Naixiu
Abstract: A porous boron-doped diamond (pBDD) was made for immobilizing gold nanoparticles on BDD facets by a special process, wherein methods of magnetron sputtering and thermal catalytic treatment were utilized. Au nanoparticles are seated in the pores of pBDD facets and could be more stable during electrochemical tests. This hybrid structure significantly improved the electrochemical properties due to the introduction of Au nanoparticles and pores, which could increase the specific surface area. The cyclic voltammetry oxidation peak current of the Au/pBDD electrode decreased with an average daily loss of 0.02 μA and maintained approximately 90.1% of its initial value after detecting dopamine once per two days for 30 days, showing an excellent long-term electrochemical stability. In addition, the Au/pBDD electrode exhibited excellent sensitivity for the detection of DA, and the limit of detection was 0.06 μM in a linear concentration range of 0.1 μM–1 mM. This work indicates that the Au/pBDD is an appropriate material for detecting DA in a long-term tests. Graphical abstract: Highlights: The porous boron doped diamond (pBDD) fabricated by thermal catalytic etching with Ni as catalyst. The Au nanoparticles-anchored porous boron doped diamond electrode is fabricated. Au nanoparticles formed and anchored inside the pores on the pBDD facets. The hybrid electrode shows long-term stability (30 days) and high sensitivity for dopamine detection.